Development of the method of exposure control of grain drying in hightemperature dryers - Volkhonov, Mikhail; Jabbarov, Igor; Soldatov, Valery; Smirnov, Ivan (Eastern-European Journal of Enterprise Technologies, 2018)
When studying the kinetics of high-temperature wheat drying, it is found that at the end of the constant drying period, there is a sharp increase in the grain heating temperature. The temperature jump occurs due to the grain surface dehydration, when the average relative moisture is close to standard and makes 15...16 %. Based on this regularity, the method of exposure control of grain drying in high-temperature dryers without using continuous-flow moisture meters is developed. The method is based on simultaneous control of the material heating temperature by temperature sensors over the entire length of the drying chamber. The measured values from the temperature sensors are transmitted to the microcontroller in order to periodically approximate them with the cubic polynomial and find the derivative of the second-order function. The microcontroller is programmed to determine the second-order critical point – the location of the grain, having standard moisture. The obtained result is compared with the maximum length of the grain path along the drying chamber in order to subsequently influence the discharger performance. The developed method of exposure control of grain drying in high-temperature dryers provides the necessary time for the temperature effect of the drying agent on the grain, process quality and reduction of energy consumption for grain drying. On the basis of this method, the drying process without the use of expensive continuous-flow grain moisture meters operating with a high measurement error is automated.